Influence of the COVID-19 pandemic on changes in aerobic fitness and injury incidence in elite male soccer players - Unnithan, V. B.; Drust, B.; Brow, C.; Bakhshi, A.; Mason, L.; Weston, M. (The Journal of Sports Medicine and Physical Fitness, 2023)
BACKGROUND: The SARS-CoV-2 agent initiated a global pandemic. The initial response to the pandemic was severe disruption to the public and private sector including sports. The resultant was that soccer clubs had to prescribe that the players trained in isolation for a prolonged period of time in an attempt to maintain fitness. The aim of the present study was to evaluate the impact of a 10-week period of training in isolation on aerobic fitness, body composition and injury incidence on the return to preseason team-training in a group of elite, male soccer players. METHODS: Twenty-two professional soccer players (age: 25.2±4.4 years) who played for an English Championship first team participated in this study. A weekly training program was sent to each player at the start of each week. Prior to the start of the isolated training period, all players underwent a maximal aerobic speed test (MAS), and Body Mass Index data (BMI) were obtained. These measurements were repeated on the return to team training. RESULTS: There was a significant (P<0.05) increase in MAS pre-post isolated training (pre: 4.71±0.15 vs. post: 4.92±0.17 m/s), no change in BMI (pre: 24.3±1.3 vs. post: 24.1±1.1 kg/m2) and a low non-contact, soft-tissue injury incidence on the return to team training. CONCLUSIONS: The evidence from this study suggests that a more prolonged preseason schedule can enhance aerobic conditioning and mitigate the injury risk on the return to competitive match-play in elite soccer players.